Optimalisasi Safety Cargo Operation pada Proses Loading Cargo Oil Product PT. Pertamina di Kapal MT. Dewi Sri - Dhawala, Pakavy Aqshall; Yudo, Hartono; Manik, Parlindungan (Jurnal Teknik Perkapalan, 2024)
Oil products fall under the category of hazardous cargo that require special handling due to the potential risks of accidents such as overflow, which can cause pollution, leakage leading to fires, worker accidents due to lack of knowledge, and claims of delays during cargo loading that can harm both companies involved. Therefore, to prevent accidents that could cause significant losses to the company, it is necessary to optimize safety procedures for cargo operations. The objective of this study is to understand the process and obstacles during the oil cargo loading on MT Dewi Sri and to analyze the hazards and risks to both workers and the cargo, ensuring the process runs more optimally. Using the HIRARC Method and Likelihood and Severity Index Method in the oil product cargo loading process, it allows for hazard level analysis and helps reduce the risk of accidents and losses. Data collection techniques include in-depth interviews, surveys, documentation, and literature reviews. The results of this study show that in the oil cargo loading process on MT Dewi Sri, 6 out of 15 activities have potential hazards and risks. After analysis, it was found that 50% were classified as High Risk, and 50% were classified as Extreme Risk before risk control measures were implemented. After risk controls were applied, the percentage of risk decreased, with 83.3% classified as Moderate Risk, and 16.6% classified as Low Risk. The handling procedures for the cargo refer to the Manual Book in accordance with the ISM Code, minimizing the risks involved